211k views
2 votes
Evaluate -3m-2e if m= 6 and e= 1.

User Qba
by
6.0k points

2 Answers

3 votes
-3m - 2e........m = 6 and e = 1

-3(6) - 2(1) =
-18 - 2 =
-20 <==
User Silverbullettt
by
5.4k points
3 votes
So, here is exactly how you would do this:

-3m-2e if m=6 and e=1

We know the values of e and m. We can plug these in to evaluate.
Simply replace the number 6 in place of m and 1 in place of e in -3m-2e

-3m-2e Original expression
-3(6)-2(1) With values plugged in
-18-2 Simplified
-20 Final answer

Our final answer would therefore be: -20

User Nasreddine Galfout
by
6.1k points